Hambatan-Hambatan yang Dialami Perusahaan Asuransi Syariah Dalam Memasarkan Produknya - Santri Yani Zainta; Nuri Aslami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
Public awareness to participate in insurance is also an obstacle for the development of sharia insurance in Indonesia. Low public awareness is a challenge for sharia insurance to provide an understanding of sharia insurance apart from the elements of maisir, gharar and usury. The level of awareness of the Indonesian people is still very low about the risks that will come in the future. This is because insurance is considered not as a primary need but as a complement to needs. The next is the community factor towards insurance. This concern can be in the form of fear if for example following insurance but when you have the misfortune of not getting a claim from the company this is usually caused by the words of other people who do not get a claim from a particular insurance company and disseminated to the general public so that it has an impact on other insurers, besides that people who have taken insurance are worried that they will not be able to pay premiums. Keywords: Sharia Insurance, Conventional Insurance, and Public Awareness.